Increased Phosphatidylserine on Blood Cells in Oral Squamous Cell Carcinoma. (July 2019) - Liu, Y.; Li, B.; Hu, T.L.; Li, T.; Zhang, Y.; Zhang, C.; Yu, M.; Wang, C.; Hou, L.; Dong, Z.; Hu, T.S.; Novakovic, V.A.; et al.
The specific function of phosphatidylserine (PS) in the context of the development of a hypercoagulable state among individuals with oral squamous cell carcinoma (OSCC) is uncertain. The goal of this study was therefore to assess the exposure of PS on microparticles (MPs) as well as on endothelial and blood cells and to assess procoagulant activity (PCA) as a function of the stage of OSCC progression. We recruited patients with OSCC ( n = 63) as well as healthy controls ( n = 26) to participate in this study. PS exposure was then assessed via confocal microscopy and flow cytometry, revealing that patients with stage III/IV OSCC exhibited higher frequencies of PS-exposing blood cells, MPs, and serum-cultured endothelial cells (ECs) than did patients with stage I/II OSCC or healthy controls. When we conducted functional coagulation assays, we discovered that PS + blood cells, MPs, and serum-cultured ECs from patients with stage III/IV OSCC mediated more rapid coagulation and more substantial production of FXa, thrombin, and fibrin as compared with controls. When samples were treated with the PS antagonist lactadherin, this resulted in an 80% disruption of PCA. Strikingly, when pre- and postoperative samples were compared from patients with stage III/IV OSCC undergoing resective surgery, PCA was significantly reduced in the postoperative samples. After stimulating ECs with inflammatory cytokines, we found by confocal microscopy that they expose PS on their cell membranes, thus generating FVa and FXa binding sites and mediating the formation of fibrin. Together our findings provide evidence that PS + blood cells and MPs are important mediators of the development of a hypercoagulable and prothrombotic state among individuals afflicted by advanced-stage OSCC. As such, a PS blockade may be a viable therapeutic strategy for treating such patients.